Inclusive Leadership and Innovative Work Behavior : The Mediating Role of Perceived Organizational Support - Nurhasanah Nasution; Syahrizal Syahrizal (Universitas Negeri Padang, 2021)
This study aims to determine the effect of inclusive leadership on innovative work behavior with the perception of organizational support as a mediator. This study uses 20 SMEs in Muara Bulian. The population in this study is MSME workers in the Muara Bulian. While the sample used is 90 employees. Data collection is done through distributing questionnaires and data processing is done through smart PLS3. The results of this study indicate that Inclusive leadership has a positive and significant effect on innovative work behavior, Inclusive Leadership has a positive and significant effect on perceptions of organizational support, perceptions of organizational support have a positive and significant effect on innovative work behavior and Inclusive Leadership has a positive and significant effect on innovative work behavior with perceptions organizational support as a mediating variable.